2021
DOI: 10.1016/j.nicl.2021.102765
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for classification of temporal lobe epilepsy with ROI-level MRI data: A worldwide ENIGMA-Epilepsy study

Abstract: Highlights Machine learning and artificial intelligence have gained popularity for medical applications. We applied support vector machine (SV) and deep learning (DL) in termporal lobe epilepsy (TLE) Structural and diffusion-based models showed similar classification accuracies. Diffusion-based models to diagnose TLE performed better or similar compared to models to lateralize TLE. Models for patients with hippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 66 publications
(68 reference statements)
5
35
0
1
Order By: Relevance
“…3A ) that was introduced in a recent study using machine learning to study the classification of temporal lobe epilepsy using multicentric ROI-level MRI data. 18 More specifically, given a set of input images where is a 2D square resolution image for participant and is the total number of participants, and a set of labels that defines the corresponding group label (e.g. HC = 0 and TLE = 1) for each participant, the following steps were sequentially applied to identify the optimal modelling parameters:…”
Section: Methodsmentioning
confidence: 99%
“…3A ) that was introduced in a recent study using machine learning to study the classification of temporal lobe epilepsy using multicentric ROI-level MRI data. 18 More specifically, given a set of input images where is a 2D square resolution image for participant and is the total number of participants, and a set of labels that defines the corresponding group label (e.g. HC = 0 and TLE = 1) for each participant, the following steps were sequentially applied to identify the optimal modelling parameters:…”
Section: Methodsmentioning
confidence: 99%
“…13 This study revealed that structural MRI and dMRI-based models had similar accuracy and that models for TLE-HS were more accurate than for MRInegative TLE. 13 While the ability of automatic quantification methods may not currently exceed visual inspection of MRIs by imaging experts in all situations, AI algorithms and tools provide important support tools and may become of great importance when such expertise is not available. Some AI tools have already been integrated into clinical care for epilepsy, 20 but it will remain important for clinicians and AI-experts to remain in close dialog for newer ML and DL approaches to be adapted for clinical use.…”
Section: Artificial Intelligence Applications For Epilepsy Diagnosis ...mentioning
confidence: 64%
“…18,19 A recent ENIGMA-Epilepsy study investigated the performance of ML and DL algorithms using structural MRI and diffusion MRI (dMRI) to classify controls vs patients with TLE with HS and MRI-negative TLE. 13 This study revealed that structural MRI and dMRI-based models had similar accuracy and that models for TLE-HS were more accurate than for MRInegative TLE. 13 While the ability of automatic quantification methods may not currently exceed visual inspection of MRIs by imaging experts in all situations, AI algorithms and tools provide important support tools and may become of great importance when such expertise is not available.…”
Section: Artificial Intelligence Applications For Epilepsy Diagnosis ...mentioning
confidence: 64%
See 1 more Smart Citation
“…In the presently highlighted study, Gleichgerrecht and colleagues leveraged ENIGMA-Epilepsy structural and diffusion-weighted MRI data using a machine learning approach to evaluate epilepsy patient and control subgroups. 4 For structural T1-weighted MRI analysis, data were collected from 16 centers and included 336 unilateral adult TLE patients and 631 matched control subjects, while diffusion data originated from 21 sites and included 863 individuals with TLE and 976 controls. Approximately 56% of TLE patients were diagnosed with left sided seizure onset, and structural T1 data were only available for patients with MTS, although diffusion data were obtained for patients with MTS and non-lesional TLE.…”
Section: Commentarymentioning
confidence: 99%